The Contested Empowerment of Kenya’s Judiciary, 2010-2015: A Historical Institutional Analysis by James Thuo Gathii - Miyawa, Maxwel (Strathmore Law Review, 2018)
There has been an increasing number of written works deconstructing various transformative values underpinned by the Constitution of Kenya. One of these transformative values is the concept of constitutional supremacy which, arguably, has not received nuanced theoretical attention in Kenya’s constitutional law scholarship. Gathii theorises the unexplored, yet controversial question of judicial empowerment and its centrality in anchoring constitutional supremacy in the post-2010 politico-constitutional order. He provides a well-researched exploratory analysis of the functional, institutional and normative fledgling nature of the Judiciary of Kenya. He does this through an analytical filter that investigates the prominent role that judicial expansion has played in promoting constitutional supremacy and the principle of legality.